2015
DOI: 10.3171/2014.11.focus14703
|View full text |Cite
|
Sign up to set email alerts
|

Update on the management of recurrent Cushing's disease

Abstract: After transsphenoidal surgery, Cushing's disease (CD) shows excellent long-term remission rates, but it may recur and pose a therapeutic challenge. Findings in recent published reports on the treatment of recurrent adrenocorticotropic hormone (ACTH)–secreting tumors suggest that repeat resection, radiation-based therapies such as Gamma Knife surgery and proton-beam radiosurgery, pharmacotherapy, and bilateral adrenalectomy all have important roles in the treatment of recurrent CD. Each of these interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Prior series have reported treatment success in 97% of nonsecreting tumors and 45 to 93% secreting adenomas, with Pollock estimating an overall success rate of durable biochemical cure in at least 60% of recurrent secreting tumors. [174][175][176][177][178][179][180] Hypopituitarism is the most common complication, with 10 to 12% of adults requiring chronic hormonal supplementation after SRS. 16,48,181,182 Data on pediatric pituitary radiotherapy is more limited, due to its infrequent use; as our literature review demonstrates, radiation of any modality was reported in only 16% of children with recurrent or persistent disease.…”
Section: Management Of Progression or Recurrencementioning
confidence: 99%
“…Prior series have reported treatment success in 97% of nonsecreting tumors and 45 to 93% secreting adenomas, with Pollock estimating an overall success rate of durable biochemical cure in at least 60% of recurrent secreting tumors. [174][175][176][177][178][179][180] Hypopituitarism is the most common complication, with 10 to 12% of adults requiring chronic hormonal supplementation after SRS. 16,48,181,182 Data on pediatric pituitary radiotherapy is more limited, due to its infrequent use; as our literature review demonstrates, radiation of any modality was reported in only 16% of children with recurrent or persistent disease.…”
Section: Management Of Progression or Recurrencementioning
confidence: 99%
“…In patients with evidence of incomplete tumor resection or a pituitary lesion on imaging, repeat TSS is recommended. Repeat TSS tends to have a lower remission rate than primary surgery, and carries with it a higher risk of panhypopituitarism (2,3). Medical therapy for CD may consist of steroidogenesis inhibitors such as ketoconazole, metyropone, mitotane, and etomidate, or pituitary-directed treatments such as pasireotide or cabergoline (1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Selective adenomectomy by TSS is the treatment of choice for Cushing’s disease [ 1 - 4 , 8 ]. The remission and recurrence rates after TSS have been reported to be in the ranges of 65%–95% and 8%–35%, respectively [ 14 - 16 ]. Several factors may influence remission in Cushing disease, such as preoperative ACTH level, UFC levels, adenoma size, localization on MRI, intraoperative tumor visualization, dural invasion, histological confirmation of corticotroph adenomas, skillful surgery, and age of patient.…”
Section: Discussionmentioning
confidence: 99%